DEVELOPING A HYBRID SUSTAINABILITY PERFORMANCE FRAMEWORK FOR ISLAMIC BANKS IN INDONESIA - Mandira, I Made Chandra; Basyariah, Nuhbatul; Hariyadi, Eko (Ekonomi Islam, 2025)
Research aims: This study aims to develop a Hybrid Sustainability Performance Index integrating Maqasid al-Shariah principles with Environmental, Social, and Governance (ESG) metrics for Islamic banks in Indonesia. Design/Methodology/Approach: The research employs Fuzzy Delphi Method (FDM) and Fuzzy Decision-Making Trial and Evaluation Laboratory (FDEMATEL) methodologies to prioritize and clarify the complex relationships between various criteria. Research findings: The integration of Maqasid al-Shariah and ESG metrics enhances the sustainability performance of Islamic banks, increases accountability and transparency to stakeholders, and supports sustainable financial growth in Indonesia. Theoretical Contribution/Originality: This study contributes to the literature by providing a structured framework that combines Islamic ethical principles with contemporary sustainability metrics, addressing a notable gap in the performance measurement of Islamic banks. Practitioners/Policy Implications: The proposed index offers Islamic banks a practical tool to align their operations with both Maqasid al-Shariah and ESG metrics, facilitating informed strategic decisions and improved stakeholder engagement. Research Limitations/Implications: While the proposed index provides a comprehensive framework, its applicability may be limited by the availability and quality of data from Islamic banks, as well as variations in the interpretation of Maqasid al-Shariah across institutions. Future research could expand the model by incorporating longitudinal data or testing the index in different regulatory and geographical contexts to enhance its robustness and generalizability.